Promoting Compassion and Self-Compassion Through Virtual Peer Support With an Artistic Journey. - Kim, Jee Hyun; Mank, Deanna; Gagliardi, Angelena (Art Therapy: Journal of the American Art Therapy Association, 2025)
This study explored the effectiveness of a virtual art-based peer support group in promoting compassion, self-compassion, and emotional well-being during the COVID-19 pandemic. It focused on the experiences of three art therapists who navigated distinct personal challenges, including isolation, injury, and grief. The virtual format allowed participants to engage in therapeutic art interventions, providing a space for self-expression, reflection, mutuality, and support. The study revealed that art-making with peer support facilitated mindfulness, emotional resilience, compassion, self-compassion and personal growth, leading to improvements in mood and a deeper connection to internal experiences. The findings suggested that art-based virtual peer support groups could offer valuable benefits during times of crisis, particularly for mental health professionals.